2014
DOI: 10.1016/j.ymeth.2013.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Investigating cockroach allergens: Aiming to improve diagnosis and treatment of cockroach allergic patients

Abstract: Cockroach allergy is an important health problem associated with the development of asthma, as a consequence of chronic exposure to low levels of allergens in susceptible individuals. In the last 20 years, progress in understanding the disease has been possible, thanks to the identification and molecular cloning of cockroach allergens and their expression as recombinant proteins. Assays for assessment of environmental allergen exposure have been developed and used to measure Bla g 1 and Bla g 2, as markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 133 publications
(189 reference statements)
0
49
0
9
Order By: Relevance
“…However few trials have shown encouraging results. [17] Suggestions for asthma control strategies at the community level include a reduction in exposure to cockroach allergen. [18] Our study reiterates that such an approach could be effective in our country given the high level of sensitisation across regions.…”
Section: Discussionmentioning
confidence: 99%
“…However few trials have shown encouraging results. [17] Suggestions for asthma control strategies at the community level include a reduction in exposure to cockroach allergen. [18] Our study reiterates that such an approach could be effective in our country given the high level of sensitisation across regions.…”
Section: Discussionmentioning
confidence: 99%
“…25 Por otro lado, Xiang y colaboradores encontraron que el moho y fumar en lugares cerrados son factores de riesgo asociados con altos niveles de ácaros del polvo. 28 El tercer grupo más frecuente en este estudio fueron los hongos: Homodendrum cladosporium y Aspergillus fumigatus (16.28 %), hallazgo superior al del estudio realizado en Monterrey, México, entre enero de 2010 y el 31 de diciembre de 2014, en el cual se encontró una prevalencia de 4.1 % para Homodendrum cladosporium y 1.7 % para Aspergillus fumigatus. 29 Esto podría deberse a diferencias climatológica: Monterrey es semiárido y Francisco Morazán posee un zona tropical cálida y húmeda.…”
Section: Discussionunclassified
“…Considering the poor quality of natural house dust mite allergen extracts, we aimed to implement a panel of purified house dust mite allergens that is as complete as possible [48][49][50]. Furthermore, several cockroach allergens were included [51,52]. The panel of pollen allergens contained allergens useful for the identification of the genuine sensitizing pollen species as well as cross-reactive allergens [53,54].…”
Section: Examples Of Detecting Early Allergen-specific Ige Responses mentioning
confidence: 99%